Lewis acid catalyzed cascade annulation of alkynols with alpha-ketoesters: a facile access to gamma-spiroketal-gamma-lactones - Kambale, Digambar A.; Thorat, Sagar S.; Pratapure, Madhukar S.; Gonnade, Rajesh G.; Kontham, Ravindar (Chemical Communications, 2017)
A novel Lewis acid catalyzed intermolecular cascade annulation of alkynols with alpha-ketoesters has been developed. This simple and efficient cascade annulation proceeds through a 5-exo-dig cyclization of alkynols followed by annulation with alpha-ketoester to provide a wide variety of unsaturated gamma-spiroketal-gamma-lactones (1,6-dioxaspiro[4.4]non-3-en-2-ones) related to many natural products.